Study of Hypoxia-inducible factor-2α expression in the malignant transformation of Oral submucous fibrosis - Joseph, Immanuel (J Oral Maxillofac Pathol, 2020)
CONTEXT: Hypoxia-inducible factor (HIF)-2α is overexpressed in primary and metastatic human cancers, whose expression is correlated with tumor angiogenesis and patient mortality. HIF plays a role in the progression of fibrosis in oral submucous fibrosis (OSF). AIM AND OBJECTIVE: The aim is to study and compare the expression of HIF-2α in OSF (a), oral squamous cell carcinoma (OSCC) with areca nut usage (b), OSCC without areca nut usage (c) and normal mucosa (d) by immunohistochemistry. SUBJECTS AND METHODS: Immunohistochemical detection of HIF-2α was done on 51 samples, which included 11 cases (a), 15 cases (b), 15 cases (c) and the expression was compared with that of (d). STATISTICAL ANALYSIS: Data were analyzed using the SPSS™ software (ver. 21.0). Chi-square test and kappa analysis were performed to compare the intensity of staining between the groups and for inter-observer agreement, respectively. Value of P ≤ 0.05 was considered statistically significant. The mean labeling index between the groups was studied by the Kruskal–Wallis test. RESULTS: All the cases of (d), (a), (b) and (c) showed HIF-2α expression (P = 0.329). About 13% cases of (c) showed intense expression (P = 0.406) and 27% of (a) cases showed expression only in the connective tissue (P = 0.023). The number of positively stained nuclei in both (b and c) cases reduced as the tumor progression was from well to poorly differentiated. CONCLUSION: Areca nut initiates fibrosis and subsequent hypoxia in OSF which triggers HIF-2α expression in the epithelium. HIF-2α could be a surrogate marker for cancer initiation and progression.